An Exploration of How the Confucian Notion of Scholar-Official has Impacted Chinese People’s View on Careers - Jie Xiong (Adult Education Research Conference, 2007)
This paper reveals that scholar-official has impacted Chinese people’s view on careers by the imperial examination system for a long history. Tensions between higher education expansion and college student employment, the meaning of scholar-official and the imperial examinations, and the implication for developing tertiary vocational education in China are discussed.